Global tax for digital platforms and its context in Mexico - Baizabal Leal, Karina (2022)
The new digital era has had a strong effect on e-commerce, eliminating borders worldwide, which implies an exponential growth in this type of innovative business, likewise it is imperative the need to update the tax rules that regulate them in order to have efficient and effective tools to support the fight against tax evasion and tax avoidance. The constitutional tax principles of equity and proportionality are a reliable guideline for the determination of global or national tax rates, therefore, a review is addressed in the 15% global digital economy tax initiative designated by the OECD. The objective of this article is to understand the progress to the application of this tax, through the study of the transition and context of the BEPS (Base Erosion and Profit Shifting) project and its context in México. The methodology is based on documentary research, with a qualitative approach and a deductive method. Finally, a reflection on the complexity of the application of the global tax rules under analysis is enunciated, envisioning an environment of uncertainty in the response of taxpayers and difficult for the Mexican legislation.